Leadership Style Analysis to Improve the Quality of Human Resources at Yayasan Pembangunan Masyarakat Sejahtera (YPMS) (Case Study at As-Salam Elementary School YPMS Kedaung) - Ading Sunarto; Agrasadya Agrasadya; Muger Apriansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Leadership style talks about how a leader applies his leadership. While the value of leadership is a principle held by leaders in the application of leadership. This study aims to analyze the leadership style applied and the application of leadership values by the leaders of the Yayasan Pembangunan Masyarakat Sejahtera (YPMS). This research also aims to: (1) To find out the leadership style at the Yayasan Pembangunan Masyarakat Sejahtera (YPMS) (2) To find out how the role of leadership in an effort to improve the quality and quality of human resources in the Yayasan Pembangunan Masyarakat Sejahtera (YPMS) ). The research method used in this research is descriptive qualitative method. Methods of data collection using interviews and participatory observation. In determining the sources using purposive sampling technique. Testing the validity of the data using source triangulation techniques. From the results of this study, it was concluded that the leadership style of the chairman of the Yayasan Pembangunan Masyarakat Sejahtera (YPMS) was a transformational, situational and authentic leadership style. While the leadership values applied are intelligence, self-confidence, perseverance, integrity, and social skills. The results of the analysis show that leaders in the Yayasan Pembangunan Masyarakat Sejahtera (YPMS) use several leadership styles to improve the quality and quality of the foundation. The role of the leader is very important in improving the quality and quality. The obstacle in its implementation is the lack of human resources, budget sources and facilities/facilities and infrastructure. This research is also planned to be published in an accredited journal sinta.